Pengaruh Dinamika Lingkungan Terhadap Daya Saing Perusahaan - Helman Fachri (Universitas Muhammadiyah Pontianak, 2013)
This study was to analyze the user's satisfaction JAMKESMAS in UPTD District Health Clinics of North Pontianak. particularly the dimensions of service quality that is composed of variable reliability, responsiveness, assurance, empathy, and tangibles. The study used survey methods, data collection techniques, namely: observation, interviews, and questionnaires. Samples used as many as 100 people by using purposive sampling. Data were analyzed using the Cartesian diagram. The results of this study indicate that the majority of respondents were satisfied with the service UPTD District Health Clinics of North Pontianak with an average satisfaction level of 4.29 and the value of the average rate of interest of 4.21 dimension of service quality the most satisfying user JAMKESMAS is the dimension of certainty guarantees, and physical evidence, where the majority of respondents' votes are in quadrant B, which means that the interest and customer satisfaction are at a high level and in accordance with the wishes of the consumer. Dimensional quality of services that they are in quadrant A, which means the consumer is not satisfied then it should be further enhanced by the company. While the dimensions of the quality of services that are in quadrant C and D in which the interests of consumers are at a low level is considered normal practice even though consumers are satisfied because it is not very important.Keywords: Satisfaction, Service Quality Dimensions Services